2021
DOI: 10.2196/28846
|View full text |Cite
|
Sign up to set email alerts
|

Informing Content and Feature Design of a Parent-Focused Human Papillomavirus Vaccination Digital Behavior Change Intervention: Synchronous Text-Based Focus Group Study

Abstract: Background Human papillomavirus (HPV) is a common and preventable sexually transmitted infection; however, vaccination rates in the United States among the target age group, which is 11-12 years, are lower than national goals. Interventions that address the barriers to and facilitators of vaccination are important for improving HPV vaccination rates. Web-based, text-based focus groups are becoming a promising method that may be well suited for conducting formative research to inform the design of d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…HPVcancerFree app (HPVCF) was designed for use by English = speaking parents of HPV vaccine-eligible patients 11–17 years of age at TCP clinics. 29–31 It is compatible with iOS and Android systems on mobile devices. HPVCF was designed to provide parent educational content to reduce barriers and increase willingness to initiate HPV vaccination among 11–17-year-old children, enable parents to record talking points regarding the HPV vaccine for discussion with the HCP at a future appointment, and to provide a reminder system for HPV vaccine dose appointments to promote completion of the series.…”
Section: Methodsmentioning
confidence: 99%
“…HPVcancerFree app (HPVCF) was designed for use by English = speaking parents of HPV vaccine-eligible patients 11–17 years of age at TCP clinics. 29–31 It is compatible with iOS and Android systems on mobile devices. HPVCF was designed to provide parent educational content to reduce barriers and increase willingness to initiate HPV vaccination among 11–17-year-old children, enable parents to record talking points regarding the HPV vaccine for discussion with the HCP at a future appointment, and to provide a reminder system for HPV vaccine dose appointments to promote completion of the series.…”
Section: Methodsmentioning
confidence: 99%
“…HPVCF was created using user-centered design principles and Intervention Mapping, an evidence-and theory-based systematic framework for developing behavior change interventions [38]. The design steps included (1) literature review and online synchronous text-based focus groups with parents from the pediatric clinic network to assess HPV attitudes, barriers, beliefs, and needs related to a digital behavior change solution [39]: (2) matrices describing target behaviors, psychosocial determinants of behavior, and change objectives; (3) delineation of theoretical methods and practical applications; (4) prototype build; (5) heuristic evaluation and in-house alpha testing; and (6) iterative user testing to assess app content, function, delivery channel, usability, value, desirability, and adoptability for both design and content. HPVCF contains 4 self-tailored components: (1) HPV A-Z, a compendium of 9 content domains providing facts about HPV and the HPV vaccine; (2) Bust-a-Myth, 7 educational modules, including peer and health care provider testimonials addressing the most salient HPV vaccination barriers; (3) Notes 4 Doc, a medium to facilitate communication with health care providers about the HPV vaccine; and (4) Get the Vax, a feature to schedule HPV vaccination appointments and receive tailored reminders (Figure 1).…”
Section: Mhealth Intervention: Hpvcancerfreementioning
confidence: 99%
“…The AVP comprises six evidence-based strategies that target clinic systems, providers, and parents (Figure 1). AVP development was guided by the Intervention Mapping systematic approach [37], informed by behavioral theory (i.e., Social Cognitive Theory [38], Theory of Reasoned Action [39], Health Belief Model) [40], and guided by formative work with clinic leadership, providers (pediatricians and medical assistants) and parents [41], to increase provider delivery of consistent, bundled (when possible), presumptive and unqualified HPV vaccination recommendations [42].…”
Section: Introductionmentioning
confidence: 99%
“…of Reasoned Action [39], Health Belief Model) [40], and guided by formative work with clinic leadership, providers (pediatricians and medical assistants) and parents [41], to increase provider delivery of consistent, bundled (when possible), presumptive and unqualified HPV vaccination recommendations [42]. We previously demonstrated that the AVP effectively increased HPV vaccination initiation in a 51-clinic pediatric network in Houston, Texas [43].…”
Section: Introductionmentioning
confidence: 99%